HUBUNGAN POLA KONSUMSI GARAM DAN KEJADIAN HIPERTENSI PADA LANSIA: TINJAUAN SISTEMATIS - Meta Zulyati Oktora; Mayang Dinda Putri; Amelia Az Zahra (Yayasan Nusantara Hasana Berdikari, 2024)
Background: Hypertension is a major non-communicable disease and one of the leading causes of death worldwide, affecting approximately 22% of the global population. It is often called the